Students’ Learning Style in Speaking Skill - Wirda Jannatul Jannah (Journal of Applied Linguistics, 2023)
This study was a descriptive qualitative study. Students' Learning Styles in Speaking Skill was the subject of this study. The goal of this study was to find out how students' learning styles affected their speaking skills. In this study, the sample consisted of one English teacher and  23 second-year students from SMPN 3 Rambah Hilir. Questionnaires (15 statements) and interviews (3 questions) were utilized by the researcher to collect data. The data was examined using the Guttman scale to determine which learning styles students preferred. According to the findings of the study, there were 22% visual learners, 69 percent auditory learners, and 9% kinesthetic learners. The major learning type was determined to be auditory. The researcher learns from the interview's results that the students use two different learning styles: visual and auditory. Keywords: Learning Style, Speaking skill